Economic Liberties and the Judiciary - Dorn, James A.; Manne, Henry G. (University Press Copublishing Division, 1988)
Essays in this volume refocus attention on Constitutional protection for economic liberties. Divided into three parts, the book deals with the following topics: Interpreting the Constitution: Theory and Practice; Property Rights, Activism and the Judicial Process; and Recent Economic Issues in the Courts.